2008
DOI: 10.1016/j.str.2008.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the Rare-Cutting Restriction Endonuclease NotI Reveal a Unique Metal Binding Fold Involved in DNA Binding

Abstract: The structure of the rare-cutting restriction endonuclease NotI, which recognizes the 8 bp target 5'-GCGGCCGC-3', has been solved with and without bound DNA. Because of its specificity (recognizing a site that occurs once per 65 kb), NotI is used to generate large genomic fragments and to map DNA methylation status. NotI contains a unique metal binding fold, found in a variety of putative endonucleases, occupied by an iron atom coordinated within a tetrahedral Cys4 motif. This domain positions nearby protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…9,10 The second and third β-strands harbour the catalytic residues of the PD…D/EXK motif, which is not absolutely conserved: the lysine is substituted by glutamic acid in BamHI and by glutamine in BglII, BstYI, 11 HinP1I, 12 and NotI. 13 Furthermore, in Bse634I, Cfr10I, EcoO109I, EcoRII, Ecl18kI, NgoMIV, and PspGI, the second carboxylate of the PD…D/EXK motif comes from a neighbouring α-helix, highlighting the importance of spatial, rather than sequence, conservation. 14,15 Finally, in SdaI, two amino acid residues separate the E and K of the PD…D/EXK motif.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The second and third β-strands harbour the catalytic residues of the PD…D/EXK motif, which is not absolutely conserved: the lysine is substituted by glutamic acid in BamHI and by glutamine in BglII, BstYI, 11 HinP1I, 12 and NotI. 13 Furthermore, in Bse634I, Cfr10I, EcoO109I, EcoRII, Ecl18kI, NgoMIV, and PspGI, the second carboxylate of the PD…D/EXK motif comes from a neighbouring α-helix, highlighting the importance of spatial, rather than sequence, conservation. 14,15 Finally, in SdaI, two amino acid residues separate the E and K of the PD…D/EXK motif.…”
Section: Introductionmentioning
confidence: 99%
“…16 The crystal structures of 19 members of the EcoRI family (Table 1), representatives of which we have studied in this paper, have been determined, including 13 co-crystal structures of enzyme-DNA complexes: BamHI, BglII, BsoBI, BstYI, Ecl18kI, EcoRI, EcoO109I, FokI, MunI, NgoMIV, NotI, PspGI, 17 and SgrAI. 7,18 Six of these co-crystal structures were determined in the presence of divalent metal ions: BamHI with Ca 2+ (cognate complex: PDB accession code 2BAM) and Mn 2+ (product complex, 3BAM), 19 BglII with Ca 2+ (cognate complex: 1DFM), 20 EcoRI with Mn 2+ (product complex: 1QPS), 21 NgoMIV with Mg 2+ (product complex: 1FIU), 22 NotI with Ca 2+ (cognate complex: 3C25), 13 and SgrAI with Ca 2+ (noncognate complex: 3DPG; cognate complex: 3DVO) and with Mn 2+ (cognate complex: 3DVO). 23 Whereas the structure analyses showed that BamHI, NgoMIV, and NotI have two divalent metal ions bound per active site (subunit), BglII and EcoRI have only one.…”
Section: Introductionmentioning
confidence: 99%
“…The two zinc metal ions in the KpnI endonuclease seem to play dual roles in both structural folding and specificity [48]. In the NotI:DNA cocrystal structure, however, four Cys residues coordinate the binding of an iron atom in a unique metal binding fold thought to be involved in protein structural stability [49]. Mutation of these individual Cys residues abolishes NotI restriction activity (PZ and SYX, unpublished results).…”
Section: Resultsmentioning
confidence: 99%
“…Alternative nuclease domains have been applied in few cases in mainly monomeric chimera [53][54][55][56][57][58] and non-FokI-based zinc finger nucleases have also been developed by introducing mutations or small modifications into the zinc finger array, such as the exchange of the metal ion-binding cysteines to histidines [59][60][61]. Trials to establish controlled artificial nucleases through lightactivation [62,63], DNA binding [64], cold-shock technique [65], protein-protein interaction [66], DNA modification [67] or metal ion dependent DNA binding [68] were also executed. Bioinformatics was utilized to predict ZFN and TALEN off-target cleavage [69].…”
Section: Current Artificial Nucleasesmentioning
confidence: 99%